Evaluation of Public Services on Community Satisfaction at the Regional Secretariat of Kepulauan Riau Province - Rivai, Nur Ilmiah (Jurnal Manajemen Pelayanan Publik, 2025)
This study aims to evaluate the quality of public services provided by the DPRD Secretariat of the Kepulauan Riau Province using a descriptive qualitative approach. The analysis is based on secondary data from the 2023 Government Performance Accountability Report (LAKIP), particularly focusing on the Community Satisfaction Index (IKM). The study interprets quantitative performance metrics through a qualitative lens using the Results-Based Evaluation (RBE) framework, examining nine service elements including service procedures, responsiveness, competency, infrastructure, and complaint handling. Respondents reported a high level of satisfaction across most service dimensions, with eight out of nine elements categorized as “Very Satisfied” based on national scoring standards (Menpan RB No. 14/2017). The highest score was recorded in the Service Implementation element (average score: 3.76), while the lowest Service Suitability received a score of 3.20, indicating a gap between service delivery and public expectations. The overall IKM score of 86.14 places the Secretariat in the “Very Good” performance category and exceeds both its 2022 score and the national average for provincial institutions. Although the findings indicate commendable public service delivery, continuous improvement is essential particularly in aligning service outcomes with community needs and expectations. Strategic recommendations include enhancing user experience audits, refining service communication standards, and expanding digital integration to increase transparency and responsiveness.